Security properties analysis in a TPM–based protocol. (30th April 2014) - Seifi, Y.; Suriadi, S.; Foo, E.; Boyd, C.
Security protocols are designed in order to provide security properties (goals). They achieve their goals using cryptographic primitives such as key agreement or hash functions. Security analysis tools are used in order to verify whether a security protocol achieves its goals or not. The analysed property by specific purpose tools are predefined properties such as secrecy (confidentiality), authentication or non–repudiation. There are security goals that are defined by the user in systems with security requirements. Analysis of these properties is possible with general purpose analysis tools such as coloured petri nets (CPN). This research analyses two security properties that are defined in a protocol that is based on trusted platform module (TPM). The analysed protocol is proposed by Delaune to use TPM capabilities and secrets in order to open only one secret from two submitted secrets to a recipient.